FROM MOTHER'S IDEAS TO THE INTERACTIONS WITH THEIR CHILDREN - Sánchez Hidalgo, José; Hidalgo García, María Victoria (Anales de Psicología / Annals of Psychology, 2003)
The aim of this paper is to study the relationship between parents’ belief about child development and parent- infant interaction. 53 mother-child interactions during feeding situation at home were analysed. The babies were 12 month-old. Parents’ belief system was evaluated by CIP (Parents’ ideas questionnaire; Palacios, 1988). Interactions were coded using some observational dimensions: emotional warm, maternal sensitivity, strategies to stimulate linguistic and autonomy development, etc. Results show significant differences in interaction style when we controlled parent’s ideas about development child and education. Mothers with modern ideas were warmer and presented more fine-tuning those mothers with traditional ideas. Results and implications belief-behaviour relationsare discussed.